Essential Oils Composition of Kaffir Lime (Citrus hystrix DC.) Collection of Bogor Botanic Gardens from Central Java and East Sumba - Inggit Puji Astuti; Kartika Dyah Palupi; Frisca Damayanti (Universitas Gadjah Mada, 2022)
The Bogor Botanical Gardens' Citrus hystrix collections from East Sumba and Central Java differ in morphology and fruit aroma compared to the common C. hystrix. Hence, this study aimed to determine the essential oils' compositions of C. hystrix originated from Central Java and East Sumba to further clarify these differences. Extraction of essential oils were done using hydro-distillation, and the chemical compositions were investigated using GC-MS. The main compound of the leaf oil from East Sumba and Central Java was Linalool and Citronellal, respectively. Meanwhile, the main constituents were almost identical for the fruit oils, namely L-β-Pinene, D-Limonene, and L-α-Terpineol.